Optimal Decision-Making in a Green Supply Chain Duopoly: A Comparative Analysis of Subsidy Strategies with Data-Driven Marketing - Yao Yao; Shaoqing Geng; Jianhui Chen; Feng Shen; Huajun Tang (Mathematics)
In the current context of severe environmental challenges and climate change, the low-carbon green development model has become an international consensus. This study establishes a green supply chain duopoly competition model, considering two types of government subsidies and data-driven marketing (DDM) to help achieve supply chain development. The aim of the research is to explore how to provide green subsidies, enhance green levels, maintain competitive advantage, and improve profits in supply chain enterprises with inconsistent green levels. The study discusses the impact of green consumer preferences, market competition, and DDM quality on the profits of supply chain enterprises. It also analyzes how to use supply chain contracts to achieve coordination and optimization within the supply chain. The findings are summarized as follows. (1) As consumer preferences for green products increase, the unit subsidy model continues to enhance performance and market share more effectively than the total subsidy model. (2) The unit subsidy model requires a more relaxed subsidy coefficient, making it easier for enterprises to develop without needing high subsidies. It consistently achieves better total performance, particularly with improved DDM quality. (3) Manufacturers and retailers can achieve a win–win situation through internal coordination of the supply chain via wholesale price contracts. (4) Under certain conditions, consumers more sensitive to green products will increase the product pricing of both M1 and M2. The level of greenness of M2 will also increase. But also, the wholesale and retail prices of M1 will decrease because of the effect of DDM. (5) The effect of the intensity of market competition on pricing decisions is more complex. Under certain conditions, the market competition coefficient has a positive impact on the pricing of M1 and a negative impact on the pricing and green level of M2. This can be changed due to an increase in the level of DDM quality, where an increase in the market competition coefficient results in lower pricing for M1 and higher pricing for M2. The green level for M2 is also improved. In addition, the improvement in DDM quality consistently has a positive impact on pricing decisions and green levels for M2. Pricing decisions for M1 are affected differently, depending on the customer’s sensitivity to DDM.